Manajemen Kurikulum Pesantren Mu’adalah Dalam Meningkatkan Kompetensi Peserta Didik di Madrasah Muallimin Tebuireng - Fadhly Ustman, Ari Setiawan, (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
In carrying out teaching and learning activities, Madrasah Mu'allimin Hasyim Asy'ari Tebuireng Islamic Boarding School uses the Mu'adalah boarding school curriculum. The author is interested in researching the implementation of the Mu'Ada Islamic boarding school curriculum, which has little presence in its application in Islamic boarding schools in Indonesia. The purpose of this study was to determine the implementation of the Mu'adalah boarding school curriculum management and the competencies possessed by students based on the implementation of the Mu'adalah curriculum management at Madrasah Muallimin Hasyim Asy'ari. This study used a qualitative approach. This qualitative research is intended to obtain descriptive data related to the implementation of Mu'adalah curriculum management at the Muallimin Hasyim Asy'ari Madrasah, whether it is oral or written information. In addition, with qualitative research the researcher will describe the empirical reality behind the implementation of Mu'adalah curriculum management and the competencies possessed by students based on the implementation of Mu'adalah curriculum management at Madrasah Muallimin Hasyim Asy'ari. The results of this study are: 1) Implementation of the curriculum at the Muallimin Hasyim Asy'ari Madrasah includes: first, good curriculum planning. Second, in implementing the curriculum from grade 1 to grade 6 there are several standards that must be met. Third, every year the Muallimin Hasyim Aya'ari Madrasah conducts teacher deliberations. 2) The competence of students can be seen from three sides, namely cognitive, effective, and psychomotor. These three aspects were well achieved through the programs in Muallimin Hasyim Asyari Tebuireng.